A hydrothermal etching route to synthesis of 2D MXene (Ti3C2, Nb2C): Enhanced exfoliation and improved adsorption performance. Issue 15 (15th October 2018) - Peng, Chao; Wei, Ping; Chen, Xin; Zhang, Yongli; Zhu, Feng; Cao, Yonghai; Wang, Hongjuan; Yu, Hao; Peng, Feng
Abstract: 2D MXenes have attracted extensive attentions owing to their anisotropy, high conductivity and other extraordinary properties. The popular preparation method of MXenes usually involves HF in high concentrations, which has seriously restricted their pervasive applications. In this work, a new hydrothermal route with low-toxicity etching agents (NaBF4, HCl) was used to synthesize Ti3 C2 MXene ( h- Ti3 C2 ). Compared with the Ti3 C2 prepared by the traditional HF etching method ( t- Ti3 C2 ), the h- Ti3 C2 has the higher c lattice parameter, larger interlayer distance and larger BET specific surface area, because of the slow release mechanism during the hydrothermal process. The hydrothermal etching method not only avoided the use of high-concentration HF, but also was more efficient to prepare Ti3 C2 flakes. Moreover, the hydrothermal etching route can be extended to other MXene materials, e.g. Nb2 C. We demonstrated that the h -MXenes have better adsorption performance of methylene blue and methyl orange dyes. The hydrothermal etching route proposed in this study enabled the environmental benign and high efficiency exfoliation of MXenes, displaying the promise to facilely prepare 2D MXenes and paving a way to their widespread applications.